Anesthetic Management and Outcome of Non-cardiac Surgery in Ischemic Heart Disease Patients - Kajal A Bhatt; Vandana S Parmar; Pringalkumar Gohil; Niyati D Maru (Academia Anesthesiologica International, 2021)
Background: Ischemic heart disease (IHD) is a leading cause of morbidity and mortality in the world and of perioperative complications in cardiac patients. Present study was done with objectives to study common coronary artery disease and their patho physiology, to identify patients at risk through history, physical examination and electrocardiogram, to evaluate the severity of underlying cardiac disease through cardiac testing taking care to minimize expenditure and to perform specialized test only on high risk patients, testing low risk patients increases cost may causes harm by delaying a non-cardiac operation. Subjects and Methods: In the present study total 60 patients (37 males & 23 females) having Ischemic heart disease were enrolled in three different groups. The study was carried out at P.D.U. Hospital, Rajkot from October 2006 to October 2008. Patients were divided into 3 different study groups according to type of anesthesia given. Group A included 20 patients received spinal and epidural anesthesia. Group B included 20 patients given peripheral nerve blockade. Remaining 20 patients were included into group C who were given general anesthesia. Various parameters of Cardiac risk index were calculated. Results: The shortest procedure in group A and group B was 30 minutes while group C had 40 minutes. The longest surgical procedure in group and group B was 145 minutes while, of the group C was 180 minutes. Prolong and major surgical procedures are more associated with the cardiac complications and mortality. Both the patients expired during surgery had developed cardiac complications. Majority of the patients were belonged to grade III & IV of ASA risk classification. Conclusion: High standard of post-operative care including pain relief and continuous ECG monitoring is required to reduce the increased morbity and mortality in susceptible patients. Choice of anesthetic technique depends up on type of surgery, duration of surgery and surgical risk factors of patients.